A Legal Analysis of Xenotransplantation in Malaysia - Farah Salwani Muda @ Ismail (Faculty of Syariah and Law, USIM, 2026)
Xenotransplantation is the transplantation of living cells, tissues, or organs from animals to humans which has emerged as a potential solution to the persistent organ shortage in Malaysia. As demand for human organs continues to exceed supply, xenotransplantation offers a promising alternative to alleviate the critical gap and reduce mortality among patients awaiting transplantation. This study adopts a library research method, examining statutory materials, scholarly literature, and policy documents to assess the existing Malaysian legal framework relevant to xenotransplantation. The analysis highlights that although Malaysia has enacted laws such as the Animal Welfare Act 2015, which regulates ethical treatment of animals, and the Biosafety Act 2007, which governs genetically modified organisms, these laws only provide fragmented and indirect regulation. They do not comprehensively address the complex ethical, biosafety, medical, religious, and liability issues uniquely associated with xenotransplantation. The findings reveal a significant regulatory gap, particularly in areas such as source animal requirements, genetic modification controls, infection risk management, consent standards, clinical trial governance, and post-transplant monitoring. In view of these shortcomings, this study proposes the establishment of a dedicated Xenotransplantation Act to provide a holistic and specialised legal framework. Such legislation would ensure patient safety, uphold ethical standards, support scientific advancement, and align Malaysia with international best practices as xenotransplantation moves closer to clinical application